WACANA KOLONIAL DALAM CERPEN LAILA KARYA PUTU WIJAYA - Yuli Mahmudah Sentana (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2021)
This study aims to describe colonial discourses that appear in a short story entitled ‘Laila’ by Putu Wijaya. It is utilizing post-colonial theory to analyze about conditions of the colonizer and colonizeddepicted in the short story. In post-colonial theory, colonized society is defined as a society that is controlled by the colonizer, either geographically, socially, or politically. Post-colonial then is used as a way to explain the actions of colonial power that are hidden behind the attitudes and practices which do not seem to show any practice of colonial authority. The results of this study indicated that the hegemonic behaviors of power by Laila's employer are found against Laila. Another discourse that emerged was the subalternate of Laila's character as the colonized whose voice was increasingly silenced. Laila's character attempts to imitate the dominant group by doing mimicry with ambivalence raised in this short story